Complete Denture Management In A Full Edentulous Patient With Mandibular Exostosis : Case Report - Sabrina Belqis Putri Salami; Pamungkas Handy; Ananda Annas Ma’ruf (CV. AFDIFAL MAJU BERKAH, 2026)
Full edentulism significantly impairs masticatory, phonetic, and esthetic functions, necessitating rehabilitation through Complete Dentures (CD). However, the functional success of a CD is often hindered by anatomical conditions such as exostosis, which can cause pressure pain and compromise the retention and stabilization of the prosthesis. This case report aims to describe the role of preprosthetic surgery, specifically alveoloplasty, in preparing an ideal supporting base for a CD. A 45-year-old female patient presented with total edentulism in both jaws for 3 years, with primary complaints of difficulty in chewing and speaking. Intraoral examination revealed a bony prominence (exostosis) in region 4, which could act as a pathological undercut. Management was performed through an alveoloplasty procedure using the envelope flap technique to reconstruct the alveolar contour to be smooth and atraumatic. Following tissue healing, a CD made of acrylic resin was fabricated to restore speech function and prevent further atrophy of the alveolar process. Preprosthetic surgical intervention proved to be crucial in achieving stability and functional comfort in the use of complete dentures.